Foreclosure auctions - Andreas Niedermayer; Artyom Shneyerov; Pia Xu (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
We develop a novel theory of real estate foreclosure auctions, which have the special feature that the lender acts as a seller for low and as a buyer for high prices. The theory yields several empirically testable predictions concerning the strategic behavior of the agents, both under symmetric and asymmetric information. Using novel data from Palm Beach County (FL, US), we find evidence of both strategic behavior and asymmetric information, with the lender being the informed party. Moreover, the data are consistent with moral hazard in mortgage securitization: banks collect less information about the value of the mortgage collateral.
Keywords: C72; D44; D82; G21; 330; Foreclosure Auctions; Asymmetric Information; Bunching; Discontinuous Strategies; Securitization